Interculturalidad y comprensión lectora en niños de educación inicial en el CECIBEB. "Silvia Guevara Pérez", para el año lectivo 2021-2022 - Yautibug Guaccha, Martha (2022)
The present thesis work allowed to strengthen interculturality and reading comprehension in children of initial education in the CECIBEB. "Silvia Guevara Pérez" aimed to develop reading comprehension by establishing interculturality based on innovative playful activities that encourage dialogue with respect for diversity. Using the methodology with a quantitative-qualitative mixed approach because with the data collected an analysis and interpretation of the information is carried out from an objective context, the data obtained the achievements were presented effectively, after the application of an innovative and didactic proposal in the fulfillment of activities in interculturality with a certain order for their progressive participation, sensitizing students in reading comprehension. In conclusion, the proposal presented is structured by means of contents with great advantages since the didactic strategies used are innovative, perfectly appropriate for the initial level, for which it is of great contribution to the integral development of the students, which was of great benefit to the professionals of education creating an impact on the teaching process.